Variasi, Keunikan, dan Penggunaan Tingkat Tutur Bahasa Jawa di Kabupaten Pacitan (Tinjauan Sosiolinguistik) - Sri Pamungkas (Jurnal Penelitian Pendidikan, 2014)
This research of speech level variaties in the Javanese language of Pacitan regency,in the multilingual context based on sociolinguistic study aims at; (1) identifying andmaking inventory of Javanese languge speech levels in Pacitan regency, (2) identifyingthe characteristics of the Javanese language speech level in Pacitan, (3) identifyingand describing the Javanese speech level in Pacitan regency pertaining to the level ofthe respect perceived by speaker toward hearer. This research is a kind of descriptivequalitative, especially investigating a case study of the variaties of Javanese languagespeech level use, in Pacitan regency. The method of this research is: (1) a method ofproviding data, with a few techniques. Those are listening, speaking, cooperating withinformants and questionnaires; (2) the method of the data analysis is managed byusing four chronological groove, namely 1) domain analysis, 2) taxonomy analysis, 3)componential analysis, and 4) cultural values analysis. Based on the research findings,the Javanese speech level in Pacitan regency is not much different from the Javaneselanguage used in Solo-Yogyakarta that is claimed to be the center of the Javaneselanguage. It can not be denied because Pacitan is closer to Solo and Yogyakarta in adistance rather than Surabaya although Pacitan regency includes East Java Province.Based on the research, Pacitan society tends to use BJK when interacting with stranger,officer, father/mother, grandfather/grandmother, uncle/aunt, both in formal and informalsituations. Ngoko Javanese language (BJN) or low level of Javanese language willbe used to interact with friends, children, underlings and servants both in formal andinformal situations. The tendency does not mean that all informants speak like that. Itis proved from the availability of the informant who says that they use BJK in formalsituations to underlings on behalf of giving appreciation for learning, especially to thechildren how they should speak in formal situations.